Pneumopericardium: A Rare Complication of Antireflux Surgery - Elisabeth, Diquas; Anne, Druez; Alexandra, Dili (Journal of Cardiology and Cardiovascular Medicine, 2023)
Pneumopericardium is a rare clinical entity, occurring in the setting of thoracic trauma, malignancies, or mechanical ventilation. Very few cases report pneumopericardium as a complication of gastrointestinal tract surgery. Signs and symptoms may be frustrating, ranging from asymptomatic to chest pain, sepsis, hemodynamic instability, pericarditis, or even cardiac tamponade. Clinical pathognomonic signs of pneumopericardium include pericardial metallic tinkling friction rub and mill wheel murmur. Diagnostic work-up includes electrocardiogram, chest radiography, and, computed tomography imaging. A gastro pericardial fistula should be considered a rare differential diagnosis for acute chest pain in patients with a history of gastroesophageal surgery. Rapid recognition and treatment avoid life-threatening complications. The successful outcome of gastro pericardial fistula treatment depends on both emergency and definitive surgical management. The survival rate with conservative management is poor. We present the case of a 78-year-old patient suffering from pneumopericardium and pericardial infusion, due to a fibrotic fistula between the Nissen’s valve, occurring 10 years after redo antireflux surgery. Treatment included broad-spectrum antibiotics, and emergency surgery for pericardial drainage, biopsy of the valve’s defect, suture, and omentoplasty.